(untitled) (Journal of actual problems of jurisprudence, 2021)
The article presents a system-wide analysis of the environmental legislation of the Republic of Kazakhstan in the field of legal protection of atmospheric air. It is especially emphasized that this vital component of the surrounding human, flora and fauna of the natural environment is still not sufficiently methodologically and legally guaranteed against negative physical, chemical, biological and other influences. In the aspect of determining the relevance of the issue under consideration, an important conclusion was also made that the norms of the Environmental Code of the Republic of Kazakhstan in relation to the protection of atmospheric air require further development and detail. In the current legal version, their potential regulatory significance is not significant, which allows us to speak both about the lack of the desired effect on their part, and about the lack of development, with the help of the national legislator, of an effective mechanism for the legal protection of atmospheric air in comparison with the protection of natural resources: land, subsoil, waters, forests, flora and fauna. The aim of the authors is to reveal the modern content of the legal protection of atmospheric air, as well as to determine the main problems and future prospects in the context of the analysis of the environmental legislation of the Republic of Kazakhstan using scientific views, domestic legislative acts and the results of law enforcement practice. During the development of the topic, the authors used a set of general scientific and special methods of scientific cognition, in particular the comparative legal method, as well as methods of modeling and system analysis. In the conclusions, the authors emphasize that one of the ways to possibly eliminate the gaps and, accordingly, create a balanced system of norms for the protection of atmospheric air on an equal basis with other natural objects can be the currently being developed and revised new edition of the Environmental Code of the Republic of Kazakhstan. Key words: atmospheric air, legal protection, environmental legislation of the Republic of Kazakhstan, environment, Environmental Code of the Republic of Kazakhstan.